Hubungan Pengetahuan Dengan Efikasi Diri Penderita Tuberkulosis Paru Di Balai Besar Kesehatan Paru Masyarakat Surakarta - Herawati, Mrs. Erni, Okti Sri Purwanti, S.Kep., M.Kep., Ns., Sp.Kep.M.B, Sahuri Teguh K, S. Kep., Ns.,M.Kep (2016)
Tuberculosis ( TB ) is a pulmonary infectious diseases that can attack the lungs. Handling of the high prevalence of TB should be taken to control the disease Pulmonary TB , one of which is the treatment. Treatment of pulmonary TB disease carried out for six to nine months. In addition to treatment to achieve a cure is very important for patients with pulmonary TB have the knowledge about the disease and have a high self-efficacy. Based on the results of the preliminary study of the incidence of pulmonary tuberculosis in Surakarta BBKPM increased by 1.06 % in 2014 compared to 2013. The purpose of this study was to determine the relationship between knowledge and self-efficacy pulmonary tuberculosis patients at the Center for Lung Health Society Surakarta. This research is a quantitative research with cross sectional approach. The method used is non-probability sampling.This research is pulmonary tuberculosis patients who underwent outpatient Polyclinic BBKPM TB who met the inclusion criteria.The samples used were 72 respondents with a sampling technique that uses accidental sampling technique. The instrument was a questionnaire of knowledge and self-efficacy has been tested on 20 patients with pulmonary tuberculosis. Non-parametric data analysis using the Spearman rho correlation coefficient test with the results showed that most of the patients are in the category of enough knowledge and most have high self-efficacy with p = 0.001 < α = 0.05 and Spearman correlation value for 0381. Conclusion that the existence of a positive and significant relationship between knowledge and self-efficacy pulmonary tuberculosis patients in Surakarta BBKPM. Suggestions for pulmonary tuberculosis patients to be able to maintain the efficacy of self-owned namely by always trying to achieve a cure. Keywords: Knowledge, self-efficacy, tuberculosis.